The book of the thousand nights and a night : a plain and literal translation of the Arabian nights entertainments. Volume ten - Burton, Richard Francis, Sir, 1821-1890; Burton, Richard Francis, Sir, 1821-1890; Leighton, Frederick, illustrator; Burton Club, publisher (Privately printed by the Burton Club, 1885)
The Book of the Thousand Nights and a Night (1885), is a celebrated English language translation of One Thousand and One Nights (the "Arabian Nights") - a collection of Middle Eastern and South Asian stories and folk tales compiled in Arabic during the Islamic Golden Age (8th−13th centuries) - by the British explorer and Arabist Richard Francis Burton (1821-1890)